The "RESEAU MATER": An efficient infection control for endometritis, but not for urinary tract infection after vaginal delivery - Louis Ayzac; Emmanuelle Caillat-Vallet; Raphaële Girard; Michel Berland (Elsevier, 2017)
Summary: "RESEAU MATER" is useful to monitor nosocomial infections in maternity and contributes to the decreasing trend of it, since its implementation. Specifically, this network demonstrates its efficiency in the control of endometritis following vaginal deliveries, but not in the control of urinary tract infections. The aim of this study is to determine whether the difference between the control of endometritis and of urinary tract infection could be explained by an unsuitable regression model or by an unsuitable care policy concerning urinary cares.This study includes (1) the analysis of historic data of the network and (2) the description of French guidelines for maternity cares and available evaluations, concerning endometritis and urinary tract infection prevention. Univariate and multivariate odds ratios (ORs) were calculated for the total study period of 1999-2013, for these infections and their risk factors.The endometritis frequency is decreasing, in association with no significant evolution of associated risk factors, but urinary tract infection frequency is constant, in association with a increasing trend of its risk factors such as intermittent catheterization and epidural analgesia.In French guidelines, all preventive measures against endometritis are clearly broadcasted by all field operators, and repeated audits have reinforced the control of their application. But preventive measures against urinary tract infection seem to be broadcasted exclusively in the circle of infection prevention agencies and not in the obstetrics societies or in the Health Ministry communication.Urinary tract infection prevention requires a clearer public and professional policy in favor of a more efficient urinary cares, with a specific target to maternity. Keywords: Urinary infection, Endometritis, Infection control, Vaginal delivery